Application of automated welding processes in the restoration of pipelines of power facilities - V. Duhanets; R. Semenyshena; P. Fedirko; V. Pukas; M. Volynkin (Machinery & Energetics)
The purpose of the study was to investigate the efficiency of automated welding processes in the restoration of pipelines of power facilities, with an emphasis on improving reliability and reducing repair time. The study used the analysis of technical literature, practical cases and the results of experimental implementation of automated welding technologies at power facilities. It was established that automated welding processes ensure high quality of welded joints in pipelines of power facilities, which significantly reduces the likelihood of defects. It was confirmed that the use of modern welding technologies helps to increase the corrosion resistance of joints and their ability to withstand high loads. Process automation has proven effective in ensuring stable welding performance, even under difficult operating conditions. It turned out that automated systems reduce the impact of the human factor, increasing the safety and reliability of work. The study also showed that automated technologies contribute to the rational use of energy resources during welding, minimise the cost of operating equipment, and ensure compliance of restored pipelines with modern technical and environmental standards. The introduction of these technologies helps to optimise repair work, reduce their duration and increase the durability of pipelines. This confirmed the feasibility of using automated welding processes to restore the infrastructure of energy facilities. It was determined that automated processes can ensure high welding accuracy, which is critical for the operation of pipelines under high pressure. The study showed that such technologies help to reduce material consumption by minimising the number of defects. In addition, the introduction of automation has proven to be an effective tool for improving the productivity of repair work and ensuring stable operation of energy systems in the long term